QUALITY OF INTERACTION AND ENVIRONMENT SUPPORT AS PERCEIVED BY FIRST-YEAR STUDENTS IN INDONESIA - Santosa, Paulus Insap (Routledge, 2022)
Campus environment and quality of interaction are two important factors that can enhance students’ ability toward their best performance in the course of their study in college. This chapter reports the descriptive statistics from these two factors in Universitas Gadjah Mada as perceived by its first-year students. The survey was conducted based on a questionnaire developed by the National Survey on Student Engagement from Indiana University and enhanced with additional questionnaires to suit the situation at Universitas Gadjah Mada. The number of 1,422 respondents came from all faculties. Six variables of interest were reported. They were ‘discussion with diverse others’, ‘community service’, ‘quality of interaction’, ‘supportive environment’, ‘social interaction’, and ‘soft skill development’. The highest and lowest mean scores for each variable generally obtained from the respective faculty that was perceived has the same characteristic in nature with the variable of interest. © 2022 selection and editorial matter, Hamish Coates, Xi Gao, Fei Guo, and Jinghuan Shi; individual chapters, the contributors.